Моделювання процесу ціноутворення на машинобудівну продукцію - Ємельянов, О. Ю.; Висоцький, А. Л.; Петрушка, Т. О. (Видавництво Львівської політехніки, 2016)
З’ясовано особливості ціноутворення на машинобудівну продукцію. Запропоновано загальний підхід до моделювання ціноутворення на машинобудівну продукцію з урахуванням параметрів попиту на товари, що виготовляються за допомогою цієї продукції. Побудовано моделі критеріальних показників оптимізації цін та обсягів збуту продукції машинобудівного підприємства. Встановлено можливості використання критеріальних показників оптимізації цін на машинобудівну продукцію для вирішення завдання вибору найкращого різновиду цієї продукції. The article deals with the features of pricing for engineering products. It is given the general approach to the modeling process of pricing for engineering products with the given parameters of the demand for goods, which are produced with the help of these products. The given approach is based on optimization of the volume of production and selling of products and, therefore, their prices. It was defined that the use of the optimization approach to determining the prices engineering products requires previous consideration of the features of their formation by predicting the impact of changes in production volumes of these products on the financial results of the enterprises which are the potential consumers. The current level of utilization of production capacities of enterprises which are potential consumers should be taken into the account in the process of price optimization and marketing of such products. Attention is drawn to the models of criteria-based indicators in price optimization and sales of products of engineering enterprises. The concept of the cost of production per unit of its productivity was defined. Using the criteria of maximum profits of the manufacturer of products for the final consumption and high profit of engineering enterprises the method of determining the price of engineering products ,which is achieved by the coordination of the interests of producer and consumer was developed. The market of the products for the final consumption, which are produced by these engineering products was described with particular attention. This market is competitive because there are a lot of manufacturers. It is proved that in this case, price optimization for engineering products must consider the condition of equality to zero of excess profits of producers of final goods. It draws our attention to the possibilities of using criteria-based indicators of price optimization for engineering products to solve the problem of selecting the best varieties of the products from several ones ,which are different in indicators of the current cost of the production and the manufacture of goods, that are produced using these engineering products. Under these conditions, the problem of finding the best model of the specific equipment needs such actions as: 1) calculating of the product cost for consumers and producer of each model of equipment, 2) using of criteria-based indicators of price optimization and sales of engineering products, the calculation of the optimal specific capital intensity of production for each model of equipment and the corresponding maximum possible value of operating profit of engineering enterprises; 3) choosing the best model of equipment for which the maximum value of the operating profit of the engineering enterprise is the largest compared to all other models. Thus, the problem of determining the optimal amounts of production and marketing of a certain kind of engineering products was reduced to the problem of finding the best level of capital intensity of the goods produced with the use of the products. The results can be used as a framework for justifying he optimal price and sales of engineering products and the selection of the best varieties of them.
Modeling of pricing on machinery products
Keywords: ціна; моделювання; машинобудівна продукція; оптимізація; критерій; попит; price; modeling; engineering products; optimization; criterion; demand